Political Education of Political Parties in Sumbawa District Ahead of The 2024 Legislative Elections - Irwansyah, Irwansyah; Kariyani, Leni Nurul; Hidayat, Rahmat (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2024)
This research provides an in-depth analysis of "Political Education of the Prosperous Justice Party in Sumbawa Regency Approaching the Legislative Election of 2024" using qualitative research methods. Through in-depth interviews with relevant informants, surveys, and data analysis, the study aims to comprehensively understand the practices of political education conducted by the Prosperous Justice Party (PKS). The research findings indicate that PKS in Sumbawa Regency recognizes the importance of political education as an integral part of preparing for the 2024 Legislative Election. The party not only plays a role as a political participant but also as an agent of political education contributing significantly to the local community's political understanding. PKS's commitment to normative values such as Pancasila and Unity in Diversity is central to shaping the party's political identity. The main challenges are encountered in efforts to change public perceptions of the party's political identity and respond to resistance to the changes in political values advocated by the party. Inhibiting factors, including inconsistent regulatory complexities, resistance to changes in values, shifts in perceptions of political identity, and differences in understanding local culture, are also identified as elements influencing the dynamics of PKS's political education. This research provides a profound understanding of PKS's political education practices and highlights challenges to be addressed to strengthen the party's political identity approaching the 2024 Legislative Election, with a specific emphasis on qualitative research methods as the analytical approach.